2019
DOI: 10.33594/000000177
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Growth and Hunger Related Genes and Physio-Biochemical Responses in Labeo rohita (Hamilton, 1822) Fed with Lysine and Betaine

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Nobari et al [ 10 ] reported betaine supplementation raised basal testosterone but did not reduce cortisol following 14 weeks of supplementation in adolescent soccer players. Betaine ingestion in pigs [ 51 ] and carp [ 52 ] has been shown to increase betaine accumulation in the hypothalamus, leading to an increase in pituitary growth hormone releasing hormone and GH. Based on the aforementioned studies, we hypothesize that betaine may also accumulate in the hypothalamus of humans, leading to greater GnRH secretion, downstream increases in testosterone, and the suppression of CRH and reduced cortisol concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Nobari et al [ 10 ] reported betaine supplementation raised basal testosterone but did not reduce cortisol following 14 weeks of supplementation in adolescent soccer players. Betaine ingestion in pigs [ 51 ] and carp [ 52 ] has been shown to increase betaine accumulation in the hypothalamus, leading to an increase in pituitary growth hormone releasing hormone and GH. Based on the aforementioned studies, we hypothesize that betaine may also accumulate in the hypothalamus of humans, leading to greater GnRH secretion, downstream increases in testosterone, and the suppression of CRH and reduced cortisol concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The activities of digestive enzymes are key regulators of the digestion and utilization of nutrients, which may be affected by diet composition (Harpaz et al, 2005; Xu et al, 2020). Previous studies revealed that proper dietary lysine might enhance digestive enzyme activities in grass carp (Li et al, 2014), Chinese sucker Muxocyprinus asiaticus (Yu et al, 2014), Indian major carp Labeo rohita (Dar et al, 2019), and rainbow trout (Ahmed & Ahmad, 2021). Similarly, the present study also showed that dietary lysine inclusion improved the overall digestive enzyme activities in the intestine and liver of H. wyckioides .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, olive flounder (Paralichthys olivaceus) (Niu et al, 2019), rainbow trout (Oncorhynchus mykiss) (Lazzarotto et al, 2018), Nile Tilapia (Oreochromis niloticus) (Wattanakul et al, 2019), Japanese seabass (Lateolabrax japonicu) (Rahimnejad et al, 2019). While, the attractants such as L-amino acids, taurine, betaine, glycine, fish meal, earthworms, Chinese herbs, and herbal extracts (Lunger et al, 2007;Shamushaki et al, 2007;Pu et al, 2017;Rufchaei et al, 2019;Xu et al, 2020) supplementation in LFM diets were considered as one of the most effective and reliable ways to improve the feed palatability (Hirt-Chabbert et al, 2012;Dar et al, 2019). But, it was also found that such odorants supplementation in fish feeds could affect the foraging behaviors of some species (Schmachtenberg, 2015).…”
Section: Introductionmentioning
confidence: 99%